Human transcriptome response to immunization with live-attenuated Venezuelan equine encephalitis virus vaccine (TC-83): Analysis of whole blood - Rebecca A. Erwin-Cohen; Aimee I. Porter; Phillip R. Pittman; Cynthia A. Rossi; Luis DaSilva (Taylor & Francis Group, 2017)
Venezuelan equine encephalitis virus (VEEV) is an important human and animal alphavirus pathogen transmitted by mosquitoes. The virus is endemic in Central and South America, but has also caused equine outbreaks in southwestern areas of the United States. In an effort to better understand the molecular mechanisms of the development of immunity to this important pathogen, we performed transcriptional analysis from whole, unfractionated human blood of patients who had been immunized with the live-attenuated vaccine strain of VEEV, TC-83. We compared changes in the transcriptome between naïve individuals who were mock vaccinated with saline to responses of individuals who received TC-83. Significant transcriptional changes were noted at days 2, 7, and 14 following vaccination. The top canonical pathways revealed at early and intermediate time points (days 2 and 7) included the involvement of the classic interferon response, interferon-response factors, activation of pattern recognition receptors, and engagement of the inflammasome. By day 14, the top canonical pathways included oxidative phosphorylation, the protein ubiquitination pathway, natural killer cell signaling, and B-cell development. Biomarkers were identified that differentiate between vaccinees and control subjects, at early, intermediate, and late stages of the development of immunity as well as markers which were common to all 3 stages following vaccination but distinct from the sham-vaccinated control subjects. The study represents a novel examination of molecular processes that lead to the development of immunity against VEEV in humans and which may be of value as diagnostic targets, to enhance modern vaccine design, or molecular correlates of protection.